2010
DOI: 10.1128/aac.01418-09
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects between Conventional Antibiotics and 2-Aminoimidazole-Derived Antibiofilm Agents

Abstract: 2-Aminoimidazoles are an emerging class of small molecules that possess the ability to inhibit and disperse biofilms across bacterial order, class, and phylum. Herein, we report the synergistic effect between a 2-aminoimidazole/triazole conjugate and antibiotics toward dispersing preestablished biofilms, culminating with a 3-orders-of-magnitude increase of biofilm dispersion toward Staphylococcus aureus biofilms. Furthermore, we document that the 2-aminoimidazole/triazole conjugate will also resensitize multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(154 citation statements)
references
References 38 publications
5
147
0
2
Order By: Relevance
“…For instance, 2-aminoimidazole derivatives targeting QS have been designed and found to disperse established biofilms [40,41]. Proof of concept studies showed that in vivo manipulation of c-di-GMP levels can effectively clear (by decreasing c-di-GMP) or prolong (by increasing c-di-GMP) Pseudomonas aeruginosa infections in murine models [42,43].…”
Section: Inducing the Natural Biofilm Dispersal Response To Control Bmentioning
confidence: 99%
“…For instance, 2-aminoimidazole derivatives targeting QS have been designed and found to disperse established biofilms [40,41]. Proof of concept studies showed that in vivo manipulation of c-di-GMP levels can effectively clear (by decreasing c-di-GMP) or prolong (by increasing c-di-GMP) Pseudomonas aeruginosa infections in murine models [42,43].…”
Section: Inducing the Natural Biofilm Dispersal Response To Control Bmentioning
confidence: 99%
“…This leads to a perpetual state of inflammation that delays wound healing (4,5). It is estimated that more than 90% of all chronic wounds contain bacteria that are biofilm associated (6), making them up to 1,000-fold more tolerant to antibiotics and the host immune response (7). Thus, taking into account the alarming increase of antibiotic-resistant bacteria, the added ability of pathogens to reside within the protection of the biofilm matrix all too often makes effective treatment of these infections impossible.…”
mentioning
confidence: 99%
“…Their resistance against most therapeutic approaches comes from multiple mechanisms, including an exopolysaccharide matrix, which functions as a barrier against penetration of antimicrobial agents (20). Therefore, for an antimicrobial agent to be effective against bacteria such as A. baumannii, it is important for the compound to possess properties which lead to the dispersion and/or disruption of biofilm structures, leading to access to bacteria, such as that seen when bacteria are in the drugsensitive planktonic form (33). To this end, we evaluated the effects of N5 on the metabolic activity of A. baumannii in biofilms via scanning electron microscopy and observed extensive dispersion and disruption of the biofilm structure compared to untreated controls.…”
Section: Discussionmentioning
confidence: 99%